Нелінійний метод гальоркіна у чисельному аналізі стаціонарних в’язких течі - Шпакович, М. О. (ХНУРЕ, 2019)
The problem of calculating the stationary flow of a viscous incompressible fluid in a bounded simply connected domain is considered. For its numerical analysis it was proposed to use the R-function method and the nonlinear Galerkin method. The results of a computational experiment for a test problem are given.
Keywords: система диференціальних рівнянь Нав’є-Стокса; плоскопаралельні течії; нелінійний метод гальоркіна; стаціонарні в’язкі течії